Free exercise programs for the elderly: a systematic review on adherence and abandonment - Nádia Souza Lima da Silva; Elizabeth Rose Assumpção Harris; Flávia Porto Melo Ferreira; Helder Guerra de Resende (Revista da Educação Física)
The elderly population in Brazil is on the rise. As a consequence, there is an equal growth in the number of free public exercise programs directed to this group. Considering the benefits of exercising and the importance of adherence to this behavior so that the benefits can be perceived, we conducted a systematic review of the existing literature on the topic, aiming to identify the reasons that lead to adherence to free public exercise programs, as well as those that lead to abandoning the same programs. Searches were conducted on SciElo, SPORTdiscus and Pubmed databases, with search phrases in Portuguese and in English. After a triage, ten studies were analyzed regarding sample characteristics, program type, data collection method and the reasons behind the subjects’ adherence and abandonment. We verified that elderly people tend to enter the projects for health-related reasons, but they remain due to other factors, such as socialization and the perception of the benefits brought on by exercising. As for abandonment, it occurs due to health problems, muscle pain due to exercising, dislike for the classes and family business.